Tele Contextual Study Development: Unfolding Case Study Using E-KOM to Improve Analytical Thinking to Content UJIKOM Ners - Tri Antika Rizki Kusuma Putri; Suci Noor Hayati; Gina Nurdina (University of Muhammadiyah Malang, 2021)
Introduction: Case-based learning is often used to maximize critical thinking skills by matching clinical cases with the body of knowledge. The use of applications that can be accessed anywhere can be an innovative learning media solution. Therefore an application called e-KOM was designed to support learning for nurse students in preparing for competency tests. Objective: This study at developing e-KOM as a learning media in clinical learning with the Tele Contextual Study method: Unfolding Case Study. Methods: The research design method used the Research and Development method. Based on Borg and Gall's stages, the researchers modified it according to the application's needs as a learning medium. They adapted the ADDIE development model, namely Analysis, Design, Development or Production or Implementation or Delivery and Evaluations. Results: This study showed that the application's feasibility level was based on validation by material and media experts. The average score of 4.4 is in the feasible category, while the user's assessment is at an average score of 85.76%, which means it is easy to use. Conclusions: e-KOM, as a nursing student learning application, is expected to improve student's learning outcomes and improve the statistical graduates in Nursing Competencies Test.